Effect of cadmium on composition and diversity of bacterial communities in activated sludges - Tsai, Yung-Pin; You, Sheng-Jie; Pai, Tzu-Yi; Chen, Ko-Wei (International biodeterioration & biodegradation, 2005)
Microbial communities of two kinds of activated sludge for removing carbon, nitrogen and phosphate (nutrient removal sludge) were identified and compared by combining cloning–denaturing gradient gel electrophoresis methods. The sludges were sampled in an anaerobic–anoxic–oxic system operating under the same conditions, except for one without the addition of cadmium (Cd0) and the other with addition of 5 mg cadmium l −1 (Cd5). Bacteria in the phylum Proteobacteria were predominant in both Cd0 and Cd5 sludges (39.6% and 35.1% of total bacteria, respectively). However, bacteria in the class Betaproteobacteria were significantly more abundant in Cd0 than in Cd5 sludge (30.7% and 2.1%, respectively). Species related to nutrient removal, such as nitrifying bacteria ( Nitrosomonas communis), floc-forming bacteria ( Zoogloea ramigera) and phosphate-accumulating organisms ( Rubrivivax gelatinosus), were the predominant species in Cd0 sludge, but were not found in Cd5 sludge. Cadmium was significantly toxic to the bacterial community in nutrient removal sludge, especially to the bacteria in the Betaproteobacteria. The comparison of microbial communities between these two kinds of sludge was further discussed in the paper.